The Impact of Overconfidence and Loss Aversion Bias on Investment Decision Making Among Users of Robo Advisors in Islamic Financial Technology - Rahmat, Tsaniya Kamilah; Sukmaningrum, Puji Sucia; Rusmita, Sylva Alif (Universitas Islam Negeri Raden Intan Lampung, 2024)
The advent of the digital age has engendered profound societal transformations, among which is the proliferation of digital investment platforms. Robo Advisors, powered by artificial intelligence, offer investment counsel to investors, promising a sense of security through judicious strategies. Robo-advisors are a cost-effective alternative to traditional financial consultants, enjoying widespread adoption due to their accessibility. This research investigates the influence of human bias on investors' irrational decision-making processes, alongside discerning potential disparities between users and non-users of robo advisors. A quantitative study was conducted to address these inquiries, involving a sample of 123 participants. Structural Equation Modeling-Partial Least Squares was employed as the data analysis technique. The findings reveal that overconfidence and loss aversion bias significantly impact the irrationality levels observed in individual investors' decision-making processes. Furthermore, no discernible differences were observed between robo-advisor users and non-users concerning the influence of overconfidence and loss aversion bias on investment decision-making within the research framework.